Thermal and Mechanical Properties of Microporous Polyurethanes Modified with Reduced Graphene Oxide - Michał Strankowski; Damian Włodarczyk; Łukasz Piszczyk; Justyna Strankowska (International Journal of Polymer Science)
Microporous polyurethanes (MPU) were modified by adding 0.25%–1.25 wt% of reduced graphene oxide (RGO). The materials were prepared without solvent via in situ polymerization. From a technological point of view, it is very important to obtain functional materials by using reacting compounds only. The thermal characteristics of obtained MPU were investigated using TGA, DSC, and DMA techniques. In comparison to nonmodified microporous polyurethane, the thermal stability and mechanical properties of the modified systems have significantly improved. The temperature corresponding to the maximum degradation rate (Tmax) for nanocomposites containing 1% and 1.25 wt% of RGO was 51°C higher than that observed for pure microporous PU system. The increase of tensile strength was also observed for matrix with the addition of 0.5 wt% RGO nanofiller.